Preventive Effects of Chitosan Coacervate Whey Protein on Body Composition and Immunometabolic Aspect in Obese Mice - Gabriel Inácio de Morais Honorato de Souza; Aline Boveto Santamarina; Aline Alves de Santana; Fábio Santos Lira; Rachel de Laquila; Mayara Franzoi Moreno; Eliane Beraldi Ribeiro; Claudia Maria da Penha Oller do Nascimento; Bruno Rodrigues; Elisa Esposito; Lila Missae Oyama (Mediators of Inflammation)
Functional foods containing bioactive compounds of whey may play an important role in prevention and treatment of obesity. The aim of this study was to investigate the prospects of the biotechnological process of coacervation of whey proteins (CWP) in chitosan and test its antiobesogenic potential. Methods. CWP (100 mg·kg·day) was administered in mice with diet-induced obesity for 8 weeks. The animals were divided into four groups: control normocaloric diet gavage with water (C) or coacervate (C-CWP), and high fat diet gavage with water (HF) or coacervate (HF-CWP). Results. HF-CWP reduced weight gain and serum lipid fractions and displayed reduced adiposity and insulin. Adiponectin was significantly higher in HF-CWP group when compared to the HF. The level of LPS in HF-W group was significantly higher when compared to HF-CWP. The IL-10 showed an inverse correlation between the levels of insulin and glucose in the mesenteric adipose tissue in the HF-CWP group. CWP promoted an increase in both phosphorylation AMPK and the amount of ATGL in the mesenteric adipose tissue in HF-CWP group. Conclusion. CWP was able to modulate effects, possibly due to its high biological value of proteins. We observed a protective effect against obesity and improved the inflammatory milieu of white adipose tissue.